Damage detection of jacket type offshore platforms using rate of signal energy using wavelet packet transform. (January 2016) - Asgarian, Behrouz; Aghaeidoost, Vahid; Shokrgozar, Hamed Rahman
Abstract: Steel jacket type offshore platforms are highly susceptible to damage because of the severe environmental condition, therefore ensuring its proper performance and detection of probable damage is very important and undeniable. In this paper, by studying on experimental results of a prototype scaled offshore platform subjected to dynamic loading for different damage conditions, efficiency of Rate of Signal Energy using Wavelet Packet Transform for damage detection of this kind of structures has been carried out. Experiments results of two support conditions including hinge based and pile supported cases have been used. Wavelet packet analysis was used to determine the location of damage for different damage scenarios. The results demonstrate that proposed method can predict location of damage accurately. It can be concluded that this method can be used for prediction of damages similar to damages considered in this paper by using a continuous measurements and monitoring of platform responses. Highlights: We build a prototype scaled offshore platform (two support condition) subjected to dynamic load. We use rate of signal energy (RSE) of wavelet packet transform as a damage index. We use measured accelerations of different sensors from experiments to compute RSE for all of damage scenarios. It was observed that RSE has desirable value for sensors near location of damage and not significant value for other sensors. By using proposed method and continuous monitoring, damage detection can be predicated with reasonable accuracy.